Copper-based graphite sealing material for aero-engine and preparation method of copper-based graphite sealing material

By using copper-based graphite sealing material with lamellar graphite orientation arrangement in aero engines, combined with porous sponge iron powder and vacuum powder mixing technology, the problem of poor lubricity of copper-based graphite sealing material is solved, and the anisotropy characteristics of the material are realized and high performance, meet the different directional performance requirements of aircraft engine sealing materials, and simplify the preparation process.

CN119114938AActive Publication Date: 2024-12-13STATE OWNED SIDA MASCH MFG CO LTD

Patent Information

Application Number
CN202411212981.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing copper-based graphite sealing materials have a large gap in performance between the copper phase and graphite in aircraft engines, resulting in poor lubricity, which affects the mechanical and tribological properties of the material, and are complex in the process, unstable in quality and high cost.

Method used

The copper-based graphite sealing material with anisotropic layered graphite is used to optimize components and preparation processes, combined with porous sponge iron powder and vacuum powder mixing technology, forming a copper-based graphite sealing material with anisotropy with high graphite content to improve the material mechanical and frictional properties.

Benefits of technology

It realizes materials that meet the performance requirements of aircraft engine sealing materials in different directions, simplifies the preparation process, reduces costs, and improves the wear and corrosion resistance of the materials, ensuring the integrity and sealing performance of the sealing materials during use. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114938A_ABST
    Figure CN119114938A_ABST
Patent Text Reader

Abstract

The invention provides a copper-based graphite sealing material for an aero-engine and a preparation method of the copper-based graphite sealing material. The copper-based graphite sealing material can meet the performance requirements of a sealing bush for the aero-engine in different directions. The material is a copper-based graphite sealing material formed by directionally arranging anisotropic lamellar graphite; the material is prepared from the following raw materials in percentage by mass: 60%-70% of copper powder, 18%-32% of iron powder, 6%-12% of graphite, 0.01%-0.5% of silicon dioxide, 0.01%-0.5% of aluminum oxide and 0.01%-0.5% of tungsten disulfide, and the sum of the mass percentages of the components is 100%. The copper powder is irregular electrolytic copper powder, the content of Cu is larger than or equal to 99.9%, and the particle size range is 48-100 microns; the iron powder is porous sponge iron powder, the content of Fe is larger than or equal to 99.9%, and the particle size range is 48-100 microns; the graphite is natural lamellar graphite, the particle size range is 48-100 [mu] m, and the thickness range is 8-18 [mu] m; the particle sizes of the silicon dioxide, the aluminum oxide and the tungsten disulfide are 2-5 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealing materials, and in particular relates to a copper-based graphite sealing material for an aero-engine and a preparation method thereof. Background Art

[0002] The dynamic seal of aircraft engines mainly adopts a non-contact grate seal structure, which uses the sudden expansion and contraction of the channel to increase the flow resistance to limit fluid leakage. It has the characteristics of high speed, high pressure, high vibration and special sealing medium. The grate seal consists of grate teeth as the rotor and a sealing bushing (also called a sealing bushing) as the stator. In general, in order to reduce seal leakage and thus improve the engine operating efficiency, the operating clearance between the rotor and the stator needs to be minimized. During service, the clearance is affected by the radial movement caused by cumulative errors, dynamic deflection and thermal deformation, and it is difficult to determine the minimum clearance during design. In order to ensure normal and stable operation when friction occurs, the sealing bushing material that allows contact friction at the non-working point is generally designed to be abradable and act as a sacrificial material. The clearance at the operating end is reduced by rotor scraping, while keeping the grate wear to a minimum. The sealing performance and operational reliability of aircraft engine comb seals depend to a large extent on the performance of the sealing bushing material. The material needs to have excellent tribological characteristics and lubrication conditions at the contact surface between the bushing and the rotor to protect the rotating parts from damage during service. It needs to have suitable physical and mechanical properties to avoid failure during service, and it needs to have good corrosion resistance to adapt to the sealing of special media.

[0003] At present, the commonly used sealing materials for comb tooth sealing bushings are: carbon / graphite sealing materials, carbon / carbon composite materials, metal alloys coated with abradable sealing coatings, powder metallurgy sealing materials, etc. Among them, copper-based graphite sealing materials are widely concerned as the preferred material for sealing medium and low temperature oil media at this stage. Copper-based graphite sealing materials are a typical composite material that can be designed according to the operating conditions to meet specific requirements, and are an important research direction in the field of sealing materials. However, due to the large gap in physical properties between copper phase and graphite and poor lubricity, the interfacial bonding performance of the two phases is poor, which seriously affects the mechanical and tribological properties of the material and limits the application of the material. At present, copper-based graphite sealing materials are mainly designed and strengthened by means of matrix reinforcement, graphite surface treatment (see Chinese patent application CN 114000007 A) or a combination of the two methods (see Chinese patent CN 107586989B, Chinese patent CN 110791676B). These methods can significantly improve the material performance, but these process methods generally have disadvantages such as complex process, unstable quality and high cost.

[0004] Therefore, for the grate seal bushing used in the lubricating oil system of an aircraft engine, a low friction coefficient and low wear amount must be ensured under the working condition that the wall surface requires high-speed sliding, and excellent mechanical properties must be possessed in the diameter direction to ensure the integrity of the installation and use process. Utilizing the designability of composite materials, the present invention has developed a copper-based graphite sealing material for aircraft engines with a simple preparation process, a short preparation cycle, and economical and reliable performance. Summary of the invention

[0005] Aiming at the difference in performance requirements for sealing bushings for aircraft engines in different directions, the present invention provides a copper-based graphite sealing material with oriented lamellar graphite for aircraft engines and a preparation method thereof, so that the material has typical anisotropy of mechanical properties and friction properties, has good mechanical properties in a direction perpendicular to the oriented arrangement direction of the lamellar graphite, and has excellent friction and wear properties in a direction parallel to the oriented arrangement direction of the lamellar graphite. The anisotropic characteristics of the material can simultaneously meet the performance requirements of the sealing material for aircraft engines in different directions, and the preparation process is simple, the cycle is short, and stable mass production is possible.

[0006] To achieve the above purpose, the technical solution provided by the present invention is:

[0007] The present invention provides a copper-based graphite sealing material for an aero-engine, which is special in that it is a copper-based graphite sealing material in which lamellar graphite is oriented;

[0008] The raw materials used for the copper-based graphite sealing material are composed of 60%-70% copper powder, 18%-32% iron powder, 6%-12% graphite, 0.01%-0.5% silicon dioxide, 0.01%-0.5% aluminum oxide and 0.01%-0.5% tungsten disulfide by mass percentage, and the mass percentage of the above components is 100%;

[0009] Because the purity and particle size of the powder will directly affect the mechanical properties and friction properties of the final product, the copper powder is an irregular electrolytic copper powder, wherein the Cu content is ≥99.9% and the particle size range is 48-100 μm;

[0010] The iron powder is porous sponge iron powder, wherein the Fe content is ≥99.9% and the particle size range is 48-100 μm;

[0011] The graphite is natural lamellar graphite with a particle size range of 48-100 μm and a thickness range of 8-18 μm;

[0012] The particle sizes of the silicon dioxide, aluminum oxide and tungsten disulfide are all 2-5 μm.

[0013] Furthermore, it is composed of 60%-65% copper powder, 26%-30% iron powder, 8%-10% graphite, 0.01%-0.3% silicon dioxide, 0.01%-0.3% aluminum oxide and 0.01%-0.3% tungsten disulfide.

[0014] Furthermore, its density is 5.8-6.4 g / cm 3 The aviation engine sealing material bushing with this density can ensure that the aviation engine comb teeth will not be damaged during use, and no fracture will occur; hardness 40-70HV;

[0015] Mechanical properties perpendicular to the arrangement direction of lamellar graphite: bending strength ≥ 120MPa; compression strength ≥ 120MPa; the mechanical properties perpendicular to the arrangement direction of lamellar graphite are higher than those parallel to the arrangement direction of graphite;

[0016] Friction performance parallel to the arrangement direction of lamellar graphite: 0.15-0.20 in dry state, 0.06-0.10 in lubricating oil medium, wear rate <2.5×10 -4 cm 3 / m; The friction performance parallel to the arrangement direction of the lamellar graphite is better than that perpendicular to the arrangement direction of the lamellar graphite.

[0017] The method for preparing the copper-based graphite sealing material for an aircraft engine is special in that it comprises the following steps:

[0018] Step 1: Powder pretreatment

[0019] 1.1 Reduction treatment and drying

[0020] Before batching, the irregular electrolytic copper powder and porous sponge iron powder are respectively reduced; the natural lamellar graphite, silicon dioxide, aluminum oxide, and tungsten disulfide powder are respectively dried to remove moisture from the powder;

[0021] 1.2 Sieving

[0022] The treated irregular electrolytic copper powder, porous sponge iron powder and lamellar graphite are sieved respectively, and the irregular electrolytic copper powder of -150 mesh to +300 mesh, the porous sponge iron powder of -150 mesh to +300 mesh and the lamellar graphite of -150 mesh to +300 mesh are taken for use;

[0023] Step 2: Mix the powder

[0024] 2.1 Weigh the irregular electrolytic copper powder, porous sponge iron powder, lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder treated in step 1 according to the mass ratio;

[0025] 2.2 Place irregular electrolytic copper powder, porous sponge iron powder and grinding balls in a ball mill for vacuum mixing, with a ball milling speed of 100-200r / min and a ball-to-material ratio of 1:1. After 3-6 hours of ball milling, place lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder in the ball mill and continue mixing for 10-20 hours to obtain a mixed powder, ensuring that each component is evenly mixed while reducing the damage to the integrity of each component particle, especially the lamellar graphite particles;

[0026] The vacuum powder mixing needs to maintain an absolute pressure of 50-80 kPa in the chamber; the grinding balls are zirconium oxide grinding balls with a diameter not greater than 0.5 mm;

[0027] Step 3: Forming

[0028] The molding process is carried out by compression molding or hot pressing;

[0029] The molding process of compression sintering is as follows:

[0030] Pour the mixed powder obtained in step 2 into a cylindrical mold / annular mold and press it under a pressure of 300-400 MPa. The pressing direction is perpendicular to the friction surface of the sealing bushing. The pressing speed is 0.1-0.5 mm / min and the holding time is 10-30 min. The density is 5.6-6.2 g / cm 3 A green blank of copper-based graphite sealing material;

[0031] The green blank is placed in a sintering furnace, a mixed gas of hydrogen and argon is used as a protective gas, the sintering temperature is 840-1000° C., and the sintering holding time is 2-3 hours to obtain a copper-based graphite sealing material;

[0032] For density <5.8g / cm 3 The samples can be re-pressed and re-fired for densification. The sintered samples are re-pressed at 200-300MPa, with a mixture of hydrogen and argon as the protective gas, a sintering temperature of 760-830℃, and a sintering time of 2-3h to obtain a density of 5.8-6.4g / cm 3 Copper-based graphite sealing materials;

[0033] The hot pressing process is as follows:

[0034] Pour the mixed powder obtained in step 2 into a cylindrical mold / annular mold, put it into a hot pressing sintering furnace, evacuate until the pressure in the furnace is less than 5kPa, the sintering temperature is 700-900℃, the sintering pressure is 20-30MPa, and the holding time is 20-50min to obtain a density of 5.8-6.4g / cm 3 Copper-based graphite sealing material.

[0035] At the same time, the present invention also provides a sealing bushing for an aircraft engine, the material of which is the copper-based graphite sealing material for the aircraft engine.

[0036] The method for preparing the sealing bushing for the above-mentioned aircraft engine is special in that, based on the above-mentioned method for preparing the copper-based graphite sealing material, step 4 is added:

[0037] The copper-based graphite sealing material for the aircraft engine is mechanically processed according to the design drawings to obtain a finished sealing bushing for the aircraft engine.

[0038] The advantages of the present invention are:

[0039] 1. The present invention provides a copper-based graphite sealing material with oriented lamellar graphite. By optimizing the components and the preparation process, a copper-based graphite sealing material with high graphite content and oriented lamellar graphite is obtained, that is, the lamellar graphite particles are evenly distributed and oriented in the material matrix. The material has typical anisotropic characteristics and good mechanical properties and friction properties, has a low friction coefficient and high wear resistance in the direction parallel to the arrangement of the lamellar graphite, and has excellent mechanical properties in the direction perpendicular to the arrangement of the lamellar graphite. It has the advantages of high strength, low friction coefficient, good wear resistance, small wear debris, etc., and no phenomenon of scraping layer falling off, falling off, and sticking occurs during use.

[0040] 2. The present invention adds an appropriate percentage of porous sponge iron powder to the copper-based graphite sealing material, introduces a harder porous iron phase into the material, and the iron phase and the graphite phase can produce a chemical metallurgical reaction at the interface to form a compound, thereby improving the bonding strength and further improving the hardness and strength of the material; the graphite chips generated during the friction process are easily filled into the pores of the porous iron phase, thereby reducing the friction coefficient of the sealing material; the porous iron phase can limit the deformation and softening of the copper phase during the friction process, thereby improving the wear resistance of the sealing material.

[0041] 3. The present invention adopts a vacuum powder mixing process to obtain uniformly distributed powder while effectively avoiding significant damage to the morphology of the softer lamellar graphite particles.

[0042] 4. The preparation method of the present invention has a simple operation process, a short preparation cycle, is economical and reliable, is easy to implement, and is suitable for large-scale industrial production.

[0043] 5. The present invention can meet the service mechanical properties of the comb seal material of the aircraft engine and at the same time ensure that the seal material has a low friction coefficient and high wear resistance on the friction surface, and has good sealing and corrosion resistance under oil and gas two-phase conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The copper-based graphite sealing bushing of Example 1;

[0045] Figure 2 This is a metallographic image of the end face of the copper-based graphite sealing bushing in Example 1;

[0046] Figure 3 This is a metallographic image of the wall surface of the copper-based graphite sealing bushing in Example 1;

[0047] Figure 4 This is the metallographic diagram of the copper-based graphite sealing material of Comparative Example 1;

[0048] Figure 5 This is the metallographic diagram of the copper-based graphite sealing material of comparative example 2. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0050] The invention provides a copper-based graphite sealing material for an aircraft engine with typical anisotropy. The copper-based graphite sealing material consists of 60%-70% of copper powder, 18%-32% of iron powder, 6%-12% of graphite, 0.01%-0.5% of silicon dioxide, 0.01%-0.5% of aluminum oxide and 0.01%-0.5% of tungsten disulfide, and the mass percentage of the above components is 100%.

[0051] In Examples 1-5, the copper powder is irregular electrolytic copper powder, wherein the Cu content is ≥99.9% and the particle size range is 48-100 μm; the iron powder is porous sponge iron powder, wherein the Fe content is ≥99.9% and the particle size range is 48-100 μm; the graphite is natural lamellar graphite, with a particle size range of 48-100 μm and a thickness range of 8-18 μm; the particle sizes of silicon dioxide, aluminum oxide and tungsten disulfide are all 2-5 μm.

[0052] Embodiment 1:

[0053] The present embodiment provides a sealing bushing for an aircraft engine, which is made of a copper-based graphite sealing material composed of the following components in percentage by mass: 60% of irregular electrolytic copper powder, 29.8% of porous sponge iron powder, 10% of natural lamellar graphite, 0.05% of silicon dioxide, 0.05% of aluminum oxide, and 0.1% of tungsten disulfide; wherein the particle size range of the irregular electrolytic copper powder, the porous sponge iron powder, and the natural lamellar graphite is 48-100 μm, and the thickness range of the lamellar graphite is 8-18 μm, and the production steps are as follows:

[0054] Step 1: Powder pretreatment

[0055] (1) Before batching, the irregular electrolytic copper powder and the porous sponge iron powder are placed in a reduction furnace for reduction treatment;

[0056] The reduction temperature of irregular electrolytic copper powder is 370℃ and the atmosphere is H 2 , the reduction reaction is kept warm for 1.5 hours and then cooled with the furnace;

[0057] The reduction temperature of porous sponge iron powder is 650℃ and the atmosphere is H 2 The reduction reaction is kept warm for 1.5 hours and then cooled with the furnace.

[0058] (2) natural lamellar graphite, silicon dioxide, aluminum oxide, and tungsten disulfide are placed in an oven for drying to remove moisture from the powder; during the drying process, the oven temperature is raised to 150° C. and kept warm for 1 hour;

[0059] (3) The treated irregular electrolytic copper powder, porous sponge iron powder, and lamellar graphite are sieved separately, and the irregular electrolytic copper powder of -150 mesh to +300 mesh, the porous sponge iron powder of -150 mesh to +300 mesh, and the lamellar graphite of -150 mesh to +300 mesh are taken for later use.

[0060] Step 2: Mix the powder

[0061] According to the stoichiometric ratio, the irregular electrolytic copper powder, porous sponge iron powder, lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide treated in step 1 are weighed; first, the irregular electrolytic copper powder, porous sponge iron powder and 0.2 mm diameter zirconium oxide grinding balls are placed in a ball mill for vacuum mixing, the absolute pressure in the chamber is maintained at 65 kPa, the ball milling speed is 120 r / min, the ball-to-material ratio is 1:1, and the ball milling time is 5 h; then, the lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powders are placed in the ball mill, and the powder mixing is continued for 15 h to obtain a mixed powder.

[0062] Step 3: Forming

[0063] The mixed powder obtained in step 2 was poured into a mold for pressing at a pressure of 350 MPa. The pressing direction was perpendicular to the friction surface of the sealing bushing. The pressing speed was 0.3 mm / min and the holding time was 15 min. The density was 5.75 g / cm 3 A green blank of copper-based graphite sealing material;

[0064] The green blank is placed in a sintering furnace, a mixed gas of hydrogen and argon is used as a protective gas, the sintering temperature is 850° C., and the sintering holding time is 2 hours, thereby obtaining the sealing bushing blank material for the aircraft engine of this embodiment;

[0065] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this embodiment are shown in Table 1.

[0066] Step 4: Machining

[0067] According to the design drawings, the sealing bushing blank material for the aircraft engine obtained in step 3 is machined to obtain Figure 1 The metallographic image of the sealing bushing end face of the copper-based graphite sealing material is as follows: Figure 2 As shown, the wall metallographic diagram is as follows Figure 3 As shown, the light gray area in the metallographic image is the copper matrix, the dark gray part with dot-like pores is iron, and the black structure is graphite.

[0068] Embodiment 2:

[0069] The present embodiment provides a sealing bushing for an aircraft engine, which is made of a copper-based graphite sealing material composed of the following components in percentage by mass: 62.6% of irregular electrolytic copper powder, 28% of porous sponge iron powder, 9% of lamellar graphite, 0.1% of silicon dioxide, 0.1% of aluminum oxide, and 0.2% of tungsten disulfide, wherein the particle size range of the irregular electrolytic copper powder, the porous sponge iron powder, and the natural lamellar graphite is 48-100 μm, and the thickness range of the lamellar graphite is 8-18 μm. The manufacturing steps are as follows:

[0070] Step 1: Powder pretreatment

[0071] (1) Before batching, the irregular electrolytic copper powder and the porous sponge iron powder are placed in a reduction furnace for reduction treatment.

[0072] The reduction temperature of irregular electrolytic copper powder is 420℃ and the atmosphere is H 2 , the reduction reaction is kept warm for 2 hours and cooled with the furnace;

[0073] The reduction temperature of porous sponge iron powder is 670℃ and the atmosphere is H 2 , the reduction reaction is kept warm for 1 hour and then cooled with the furnace.

[0074] (2) Place natural lamellar graphite, silicon dioxide, aluminum oxide, and tungsten disulfide in an oven for drying to remove moisture from the powder. During the drying process, raise the oven temperature to 180°C and keep it warm for 1.5 hours;

[0075] (3) The treated irregular electrolytic copper powder, porous sponge iron powder, and lamellar graphite are sieved separately, and the irregular electrolytic copper powder of -150 mesh to +300 mesh, the porous sponge iron powder of -150 mesh to +300 mesh, and the lamellar graphite of -150 mesh to +300 mesh are taken for later use.

[0076] Step 2: Mix the powder

[0077] Weigh the irregular electrolytic copper powder, porous sponge iron powder, lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder treated in step 1 according to the stoichiometric ratio; first put the irregular electrolytic copper powder, porous sponge iron powder and 0.2mm diameter zirconium oxide grinding balls into a ball mill for vacuum mixing, maintain the absolute pressure in the chamber at 60kPa, the ball milling speed at 180r / min, the ball-to-material ratio at 1:1, and the ball milling time for 4h; then put the lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder into the ball mill, continue mixing for 12h to obtain a mixed powder.

[0078] Step 3: Forming

[0079] The mixed powder obtained in step 2 was poured into a mold for pressing at a pressure of 400 MPa. The pressing direction was perpendicular to the friction surface of the sealing bushing. The pressing speed was 0.2 mm / min and the holding time was 10 min. The density was 5.68 g / cm 3 The green billet of copper-based graphite sealing material.

[0080] The green blank was placed in a sintering furnace, and a mixture of hydrogen and argon was used as the protective gas. The sintering temperature was 900°C, and the sintering holding time was 2h. The density was 5.75g / cm 3 The copper-based graphite sealing material sample. Since the density does not reach 5.8g / cm 3 The sintered sample was subjected to 250MPa re-pressing, a mixed gas of hydrogen and argon was used as the protective gas, the sintering temperature was 800°C, and the sintering holding time was 2h to obtain the sealing bushing blank material for the aircraft engine of this embodiment;

[0081] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this embodiment are shown in Table 1.

[0082] Step 4: Machining

[0083] According to the design drawings, the sealing bushing blank material for the aircraft engine obtained in step three is machined to obtain a finished sealing bushing.

[0084] Embodiment 3:

[0085] The present embodiment provides a sealing bushing for an aircraft engine, which is made of a copper-based graphite sealing material composed of the following components in percentage by mass: 65% of irregular electrolytic copper powder, 26.7% of porous sponge iron powder, 8% of lamellar graphite, 0.05% of silicon dioxide, 0.1% of aluminum oxide, and 0.15% of tungsten disulfide, wherein the particle size range of the irregular electrolytic copper powder, the porous sponge iron powder, and the lamellar graphite is 48-100 μm, and the thickness range of the lamellar graphite is 8-18 μm. The manufacturing steps are as follows:

[0086] Step 1: Powder pretreatment

[0087] (1) Before batching, the irregular electrolytic copper powder and the porous sponge iron powder are placed in a reduction furnace for reduction treatment.

[0088] The reduction temperature of irregular electrolytic copper powder is 400℃ and the atmosphere is H 2 , keep the reduction reaction warm for 1 hour and cool with the furnace;

[0089] The reduction temperature of porous sponge iron powder is 620℃ and the atmosphere is H 2 , the reduction reaction is kept warm for 2 hours and then cooled with the furnace.

[0090] (2) Natural lamellar graphite, silicon dioxide, aluminum oxide, and tungsten disulfide are placed in an oven for drying to remove moisture from the powder. During the drying process, the oven temperature is raised to 150°C and kept warm for 1 hour.

[0091] (3) The treated irregular electrolytic copper powder, porous sponge iron powder, and lamellar graphite are sieved separately, and the irregular electrolytic copper powder of -150 mesh to +300 mesh, the porous sponge iron powder of -150 mesh to +300 mesh, and the lamellar graphite of -150 mesh to +300 mesh are taken for later use.

[0092] Step 2: Mix the powder

[0093] According to the stoichiometric ratio, the irregular electrolytic copper powder, porous sponge iron powder, lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide treated in step 1 are weighed; first, the irregular electrolytic copper powder, porous sponge iron powder and 0.2 mm diameter zirconium oxide grinding balls are placed in a ball mill for vacuum mixing, the absolute pressure in the chamber is maintained at 80 kPa, the ball milling speed is 200 r / min, the ball-to-material ratio is 1:1, and the ball milling time is 3 h; then, the lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powders are placed in the ball mill, and the powder mixing is continued for 10 h to obtain a mixed powder.

[0094] Step 3: Forming

[0095] Pour the mixed powder obtained in step 2 into a mold, put it into a hot pressing sintering furnace, evacuate the furnace to a pressure of 3 kPa, set the sintering temperature to 800°C, set the sintering pressure to 25 MPa, and keep the temperature for 25 min. Then, cool it down and take it out of the furnace to obtain the sealing bushing blank material for the aircraft engine of this embodiment.

[0096] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this embodiment are shown in Table 1.

[0097] Step 4: Machining

[0098] According to the design drawings, the sealing bushing blank material for the aircraft engine obtained in step three is machined to obtain a finished sealing bushing.

[0099] Example 4

[0100] This embodiment provides a sealing bushing for an aircraft engine, which is different from the first embodiment in that the formula is changed to contain a higher percentage of copper powder and a lower percentage of iron powder. Irregular electrolytic copper powder 70%, porous sponge iron powder 18%, lamellar graphite 11.8%, silicon dioxide 0.05%, aluminum oxide 0.05%, tungsten disulfide 0.1%.

[0101] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this embodiment are shown in Table 1.

[0102] Example 5

[0103] This embodiment provides a sealing bushing for an aircraft engine, which is different from the embodiment 1 in that the formula is changed and contains a lower percentage of graphite powder: 61.6% irregular electrolytic copper powder, 32% porous sponge iron powder, 6% lamellar graphite, 0.1% silicon dioxide, 0.1% aluminum oxide, and 0.2% tungsten disulfide.

[0104] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this embodiment are shown in Table 1.

[0105] Comparative Example 1

[0106] This comparative example provides a sealing bushing for an aircraft engine. Other conditions are the same as those of Example 1, except that the cold isostatic pressing process is used for forming. Figure 4 .

[0107] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this comparative example are shown in Table 1.

[0108] Comparative Example 2

[0109] This comparative example provides a sealing bushing for an aircraft engine. Other conditions are the same as those of Example 1, except that granular graphite with a particle size range of 48-100 μm is used instead of lamellar graphite with a particle size range of 48-100 μm and a thickness range of 8-18 μm. Figure 5 .

[0110] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this comparative example are shown in Table 1.

[0111] Comparative Example 3

[0112] This comparative example provides a sealing bushing for an aircraft engine. Other conditions are the same as those of Example 1. The difference from Example 1 is that the formula of this comparative example does not contain iron powder.

[0113] The main physical, mechanical and friction properties of the copper-based graphite sealing material of this comparative example are shown in Table 1.

[0114] Table 1 Comparison of physical, mechanical and friction properties of copper-based graphite sealing materials

[0115]

[0116]

[0117] It can be seen from Table 1 in combination with the embodiments and comparative examples of the present invention that the copper-based graphite sealing materials prepared in Examples 1-5 of the present invention exhibit relatively excellent mechanical properties in a direction perpendicular to the arrangement direction of the lamellar graphite and relatively excellent friction properties in a direction parallel to the arrangement direction of the lamellar graphite, meeting the use requirements of the engine sealing bushing.

[0118] Compared with Example 1, in Comparative Example 1, compression molding is replaced by isostatic pressing, and in Comparative Example 2, lamellar graphite is replaced by granular graphite; the materials obtained by Comparative Examples 1 and 2 have the same microstructure in all directions (metallographic images are shown in FIG. Figure 3 and Figure 4 The mechanical properties and friction properties in all directions are consistent, and the mechanical properties of Comparative Examples 1 and 2 are lower than those of Example 1 perpendicular to the arrangement direction of the lamellar graphite, and the friction coefficients of Comparative Examples 1 and 2 are higher than the friction coefficient of Example 1 parallel to the arrangement direction of the lamellar graphite, indicating that the anisotropic copper-based graphite sealing material with directional arrangement of lamellar graphite has better performance in a specific direction than the isotropic material under the same conditions.

[0119] Compared with Example 1, no iron phase is added in Comparative Example 3. It can be seen that the introduction of the porous iron phase not only enhances the hardness and mechanical properties of the material to a certain extent, but also reduces the friction coefficient of the material and improves the wear resistance of the material.

[0120] In summary, through the optimization of the present invention, a high-graphite-content copper-based graphite sealing material with oriented lamellar graphite is obtained, so that the material has typical anisotropy of mechanical properties and friction properties, good mechanical properties in the direction perpendicular to the oriented arrangement direction of the lamellar graphite, and excellent friction and wear properties in the direction parallel to the oriented arrangement direction of the lamellar graphite. The anisotropic characteristics of the material can simultaneously meet the performance requirements of aircraft engine sealing materials in different directions.

[0121] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.

Claims

1. A copper-based graphite sealing material for an aircraft engine, characterized in that: It is a copper-based graphite sealing material with anisotropic lamellar graphite directional arrangement; The raw materials used for the copper-based graphite sealing material are composed of 60%-70% copper powder, 18%-32% iron powder, 6%-12% graphite, 0.01%-0.5% silicon dioxide, 0.01%-0.5% aluminum oxide and 0.01%-0.5% tungsten disulfide by mass percentage, and the mass percentage of the above components is 100%; The copper powder is an irregular electrolytic copper powder, wherein the Cu content is ≥99.9% and the particle size range is 48-100 μm; The iron powder is porous sponge iron powder, wherein the Fe content is ≥99.9% and the particle size range is 48-100 μm; The graphite is natural lamellar graphite with a particle size range of 48-100 μm and a thickness range of 8-18 μm; The particle sizes of silicon dioxide, aluminum oxide and tungsten disulfide are all 2-5 μm.

2. The copper-based graphite sealing material according to claim 1, characterized in that: It consists of 60%-65% copper powder, 26%-30% iron powder, 8%-10% graphite, 0.01%-0.3% silicon dioxide, 0.01%-0.3% aluminum oxide and 0.01%-0.3% tungsten disulfide.

3. The copper-based graphite sealing material for aircraft engines according to claim 1 or 2, characterized in that: Its density is 5.8-6.4g / cm 3 , hardness 40-70HV; Mechanical properties perpendicular to the arrangement direction of lamellar graphite: bending strength ≥ 120MPa; compression strength ≥ 120MPa; Friction performance parallel to the arrangement direction of lamellar graphite: 0.15-0.20 in dry state, 0.06-0.08 in lubricating oil medium, wear rate <2.5×10 -4 cm 3 / m.

4. The method for preparing the copper-based graphite sealing material for aircraft engines according to claim 1, characterized in that: The following steps are involved: Step 1: Powder pretreatment 1.1 Reduction treatment and drying Before batching, the irregular electrolytic copper powder and porous sponge iron powder are respectively reduced; the natural lamellar graphite, silicon dioxide, aluminum oxide, and tungsten disulfide powder are respectively dried to remove moisture from the powder; 1.2 Sieving The treated irregular electrolytic copper powder, porous sponge iron powder and lamellar graphite are sieved respectively, and the irregular electrolytic copper powder of -150 mesh to +300 mesh, the porous sponge iron powder of -150 mesh to +300 mesh and the lamellar graphite of -150 mesh to +300 mesh are taken for use; Step 2: Mix the powder 2.1 Weigh the irregular electrolytic copper powder, porous sponge iron powder, lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder treated in step 1 according to the mass ratio; 2.2 Place irregular electrolytic copper powder, porous sponge iron powder and grinding balls in a ball mill for vacuum mixing, with a ball milling speed of 100-200 r / min and a ball-to-material ratio of 1:

1. After ball milling for 3-6 hours, place lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder in the ball mill and continue mixing for 10-20 hours to obtain a mixed powder; The vacuum powder mixing chamber must maintain an absolute pressure of 50-80 kPa; the grinding balls are zirconium oxide grinding balls with a diameter not greater than 0.5 mm; Step 3: Forming The molding process is carried out by compression molding or hot pressing; The molding process of compression sintering is as follows: Pour the mixed powder obtained in step 2 into a cylindrical mold / annular mold and press it under a pressure of 300-400 MPa. The pressing direction is perpendicular to the friction surface of the sealing bushing. The pressing speed is 0.1-0.5 mm / min and the holding time is 10-30 min. The density is 5.6-6.2 g / cm 3 A green blank of copper-based graphite sealing material; The green blank is placed in a sintering furnace, a mixed gas of hydrogen and argon is used as a protective gas, the sintering temperature is 840-1000°C, and the sintering holding time is 2-3h to obtain a copper-based graphite sealing material; For density <5.8g / cm 3 The samples should be re-pressed and re-fired for densification. The sintered samples are re-pressed at 200-300MPa, with a mixture of hydrogen and argon as the protective gas, a sintering temperature of 760-830℃, and a sintering time of 2-3h to obtain a density of 5.8-6.4g / cm 3 Copper-based graphite sealing materials; The hot pressing process is as follows: Pour the mixed powder obtained in step 2 into a cylindrical mold / annular mold, put it into a hot pressing sintering furnace, evacuate until the pressure in the furnace is less than 5kPa, the sintering temperature is 700-900℃, the sintering pressure is 20-30MPa, and the holding time is 20-50min to obtain a density of 5.8-6.4g / cm 3 Copper-based graphite sealing material.

5. The method for preparing the copper-based graphite sealing material for aircraft engines according to claim 4, characterized in that: In step 1.1, the irregular electrolytic copper powder and the porous sponge iron powder are placed in a reduction furnace for reduction treatment respectively; Among them, the temperature for reduction of irregular electrolytic copper powder is 350-450℃, the atmosphere is H2, the heating rate is 100-120℃ / h, the insulation time of reduction reaction is 1-3h, and it is cooled with the furnace; the temperature for progressive reduction of porous sponge iron powder is 600-700℃, the atmosphere is H2, the heating rate is 120-150℃ / h, the insulation time of reduction reaction is 1-2h, and it is cooled with the furnace; Place natural lamellar graphite, silicon dioxide, aluminum oxide and tungsten disulfide powder in an oven for drying, raise the oven temperature to 150-200°C and keep it warm for 1-2 hours.

6. The method for preparing the copper-based graphite sealing material for aircraft engines according to claim 4 or 5, characterized in that: In step 2.2, ball milling was performed for 5 h.

7. A sealing bushing for an aircraft engine, characterized in that: The material is the copper-based graphite sealing material for aircraft engines as described in any one of claims 1-3.

8. The method for preparing the sealing bushing for an aircraft engine according to claim 7, characterized in that: On the basis of the copper-based graphite sealing material preparation method, step 4 is added: The copper-based graphite sealing material for the aircraft engine is mechanically processed according to the design drawings to obtain a finished sealing bushing for the aircraft engine.

Citation Information

Patent Citations

  • Copper-base powder metallurgy friction material for high-speed linear brake and preparing method of copper-base powder metallurgy material

    CN107245676A

  • Copper-based powder metallurgical friction material for high-energy braking

    CN111961912A

  • Copper-based composite friction material containing modified sepiolite as well as preparation method and application of copper-based composite friction material

    CN117448623A

  • Copper-based powder metallurgy friction material containing nitride and preparation method thereof

    CN117620158A

  • Ternary modified multiphase ceramic powder reinforced copper-based powder metallurgy friction material

    CN118389896A

Cited By

  • Multi-component composite powder for abradable seal coating and preparation method of multi-component composite powder

    CN119839286A